The choice of the optimal temperature and time parameters of gas nitriding of steel - Dhafer, Wadee Al-Rekaby; Kostyk, Viktoriia; Kostyk, Kateryna; Glotka, Alexandr; Chechel, Mykola (Eastern-European Journal of Enterprise Technologies, 2016)
Mathematical modeling of the gas nitriding process allows solving the problems of control of process parameters, prediction of outcomes and development of various treatment conditions, which is quite an urgent issue today. The research was aimed at selecting the optimum temperature and time parameters of gas nitriding of 38Сr2MoAl steel. Optical and electron microscopy showed that the diffusion layer after gas nitriding in the ammonia environment is the nitrided case and the region of internal nitriding. The experimental data showed that the diffusion layer depth varies from 40 to 650 µm in the range of gas nitriding temperatures of 500 - 560 °С and time of 20 - 80 hours, while the surface hardness varies within 6.5 - 10 GPa. The mathematical models in the form of quadratic polynomials, describing the dependence of the depth of the nitrided case and the surface hardness on the temperature and time of gas nitriding were obtained. The mathematical description of the changes in the depth of the nitrided case and surface hardness depending on the changes in the treatment temperature and time, which allows determining the specific conditions of the gas nitriding (temperature and time) based on the desired depth of the diffusion layer or the surface hardness of 38Сr2MoAl steel was constructed.